Global maritime distress and safety system (GMDSS). Cospas-Sarsat EPIRB. Emergency position indicating radio beacon operating on 406 MHz. Operational and performance requirements, methods of testing and required test results Part 2, (2nd July 2021) - British Standards Institution,
No abstract available